2019
DOI: 10.2217/fon-2019-0403
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New GLDC Gene Alternative Splicing Variant and its Protumorigenic Roles in Lung Cancer

Abstract: Aim: To clarify the regulatory roles of GLDCV1, the first identified truncated glycine decarboxylase (GLDC), on cancer stem cells and tumorigenesis. Materials & methods: RT-PCR or RT-qPCR, immunoblotting and immunohistochemical staining were applied to assess gene expression. MTT, BrdU incorporation and colony formation assays were used to examine cell proliferation capacity. Soft agar colony formation and in vivo transplantation were applied to evaluate cellular transformation and tumorigenesis. Results &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…GLDC, a key enzyme in the glycine cleavage system, is involved in glycine metabolism and the conversion of glycine into a one-carbon unit, thereby enhancing glucose metabolism, energy metabolism, and other metabolic processes [ 18 , 19 , 20 ]. Prior research demonstrates that elevated expression of GLDC boosts cell proliferation, reinforces cell antioxidant capacity, improves cell survival, and significantly expedites the development of an organism’s tissues and organs [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…GLDC, a key enzyme in the glycine cleavage system, is involved in glycine metabolism and the conversion of glycine into a one-carbon unit, thereby enhancing glucose metabolism, energy metabolism, and other metabolic processes [ 18 , 19 , 20 ]. Prior research demonstrates that elevated expression of GLDC boosts cell proliferation, reinforces cell antioxidant capacity, improves cell survival, and significantly expedites the development of an organism’s tissues and organs [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although GLDC has been demonstrated to participate in regulating the development of tumors in some types of cancers, its roles in different cancers are controversial and not always consistent. Previous studies have shown that GLDC overexpression or its gene alternative splicing enhances cellular transformation and tumorigenesis and is correlated with poorer survival in nonsmall cell lung cancer (NSCLC) (6,13). Inhibition of GLDC transcript represses cell proliferation and colony formation in NSCLC and prostate cancer cells (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…GLDC is the P protein in the glycine cleavage system and can be combined with glycine to transfer the methylamine group of glycine to the T protein [ 158 ]. GLDC participates in the first and rate-limiting step of glycine decomposition [ 157 ].…”
Section: Another Seven N-myc Target Genesmentioning
confidence: 99%